Empowerment Strategies Through Coaching Interventions on Controlling Blood Sugar Levels the Elderly - Desi Deswita; Sefrizon Sefrizon; Anita Mirawati; Zulharmaswita Zulharmaswita; Yudistira Afconneri; Deharnita Deharnita; Yulvi Hardoni (Indonesian Journal of Global Health Research, 2020)
The problem of elderly diabetes mellitus is complex and various interventions in the form of education have been carried out in controlling blood sugar levels but the results have not been optimal. Based on this, the researcher wants to know the effect of coaching intervention on controlling blood sugar levels of the elderly with diabetes in Indonesia. The quasi-experimental research design uses a treatment group. Sampling with consecutive sampling in which the intervention group was selected according to purpose, with 38 respondents. Independent t-test was used. The results obtained were significant differences in blood sugar levels after being given an intervention. Coaching interventions affect blood sugar levels of the elderly with diabetes. It was concluded that coaching interventions reduce blood sugar levels and provide opportunities for nurses to develop promotive and preventive efforts. Keywords: blood glucose levels, coaching intervention, elderly